2004
DOI: 10.1111/j.1600-0722.2004.00161.x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between bacterial infection and evaluation using a laser fluorescence device, DIAGNOdent

Abstract: The aim of this in vitro study was to investigate the relationship between bacterial infections in carious dentin when detected by two different methods -- polymerase chain reaction (PCR), and a laser fluorescence device, DIAGNOdent. Dentin was removed every 300 micro m in the direction of the pulp chamber in 10 extracted molars with occlusal dentin caries and 3 extracted sound molars. Dentin surfaces were evaluated using DIAGNOdent, and dentinal tissue samples were removed by using a round bur before and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 24 publications
1
28
0
Order By: Relevance
“…DIAGNOdent measures fluorescence from caries lesions that is thought to originate from bacterial metabolites 14) , and this fluorescence closely correlates with estimates of bacterial prevalence in these lesions 15,16) . DIAGNOdent is thus considered a gold standard for measuring the progression of caries.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…DIAGNOdent measures fluorescence from caries lesions that is thought to originate from bacterial metabolites 14) , and this fluorescence closely correlates with estimates of bacterial prevalence in these lesions 15,16) . DIAGNOdent is thus considered a gold standard for measuring the progression of caries.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study 15) , we found that bacteria were not detectable by PCR when DIAGNOdent gave values of <15.6 in active caries lesions. Substituting this value into the regression formula derived in this study (HK=0.419+238.342/D), this equates to a limit of bacterial detection of HK=15.7.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations